National strategies for implementing lifelong learning (LLL) - the gap between policy and reality : an international perspective - Bengtsson, Jarl [Verfasser] (My University, 2013)
"In this article, the late Jarl Bengtsson briefly traces the evolution of the concept of lifelong learning within the member states of the Organisation for Economic Co-operation and Development (OECD). He points out that on the one hand lifelong learning is accepted, in policy terms, by all OECD countries and many other countries, but on the other hand there is an uneven and slow pace of implementation of lifelong learning. He examines three main reasons for this, namely the lack of workable implementation strategies, the lack of a funding system and stakeholders' resistance to change. Without denying that each country is different and has to develop its own strategy, Bengtsson identifies a certain number of policy and research issues common to all countries, which are relevant to the acceleration of the implementation of lifelong learning strategies and programmes. Based on a paper originally presented at the Asia European Meeting (ASEM) Conference in Beijing in November 2009, this article closes with a reflection about where lifelong learning might be in 40 years' time. Jarl Bengtsson updated his seminal paper in 2012 for inclusion in this special issue on lifelong learning, taking into account recent developments such as the establishment of learning societies." (Author's abstract, BIBB-Doku)
An earlier version of this paper was published online by PASCAL International Observatory in 2009 under the title "National Strategies for Implementing Life Long Learning (LLL): An international perspective", http://pobs.cc/2s7 (last accessed 09 December 2013)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 4 Kosten & Finanzierung; I 2.2 Europa; Weiterbildungspolitik; Lebenslanges Lernen; Weiterbildungsfinanzierung; Internationaler Vergleich; Europa